Use of the computer program "Fitball training" for the improvement of organization of the health - improving studies with the women of the first mature age with the use of fitball. - Ljadskaja O.Yu (Kharkov National Pedagogical University, 2010)
Efficiency of the use of the computer program is considered at employments health - improving studies with women. In experiment 60 women took part in the age 21-35 years. It is set that the use of the computer program allowed to control efficiency of the chosen training. It is shown that at training loading on a spine and lower limbs was minimum. It is well-proven, that specific loading at employments with the use of fitball positively influenced on the anthropometric indexes of women of the first mature age.